Штатний співробітник vs приватний підприємець (ФОП) в українській сфері IT - Кіреєва, Софія Олександрівна (Гуманітарні аспекти цифрового суспільства : тези доп. учасників міжн. наук.-практ. конф. (Харків, 8 груд. 2022 р.), 2022)
This article focuses on the comparative analysis of the responsibilities of the self-employed and the employee in such a dynamic field as information technology (IT). A huge number of programmers in Ukraine are employed as private entrepreneurs. Many understand that this is not quite a job and there are considerable risks, but not everyone is aware of this for sure. Thus, we can talk about one of the most important problems, namely the protection of the rights of IT professionals, who are probably the future of our country.